Ci, Mãe do Mato: the inverted myth of the amazons in Macunaíma and the modernist project - Redel, Elisangela (Manuscrítica: Revista de Crítica Genética, 2016)
The present text is divided in two parts: in the first one, I bring general and introductory considerations on Mário de Andrade, his archive of literary creation and the critical assimilation that was made from other texts, as the ones by German ethnologist Theodor Koch- Grünberg in the writing of Macunaíma: o herói sem nenhum caráter (1978). In the second moment of this work, I discuss the representation of the myth of warrior amazons in the third chapter of the rhapsody, which is called Ci, Mãe do Mato, using some correspondences which make part of the auxiliary material for the interpretation of the work. In Andrade’s writing style, the myth of the amazons is decolonized, because it receives other routes and elements which distort its funding characteristics. In other words, Mário denies the copy upon using the classical version of the myth in an anthropophagic way. From this perspective, Mário lends the Brazilian icamiaba a sexual connotation, since the amazon loses her characteristic of warrior and ravishingly surrenders to the pleasures of love with the hero. This critical assimilation is registered in the aesthetical and ideological modernist project, but it also resounds elements from the German Expressionism, whose vanguard Mário would have been influenced by in the recognition of the primal myth.